2024
DOI: 10.3390/educsci14020119
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress and Anxiety among Portuguese Students: The Role of Perceived Social Support and Self-Management

Ana Pontes,
Vera Coelho,
Carla Peixoto
et al.

Abstract: Adolescents are experiencing increasing levels of anxiety and academic stress, with schools being privileged contexts to foster mental health literacy and hinder stress and anxiety. Social support and self-management skills have been described as protective factors for these phenomena. Therefore, this cross-sectional study examines the relations between social support, self-management skills, academic stress, and anxiety among adolescents, analyzing the mediational role of self-management in the relation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Studies have indicated that undergraduate healthcare students have a higher score of emotional intelligence when assessed using the same measurement scale SSREIT [33] [55] . Furthermore, our study found that students experience a moderate level of stress, which aligns with a previous study that deployed the same PAS scale to measure academic stress in adolescents [45]. These ndings are in the same vein with a study carried out in Morocco by Ksiksou et al in 2023, which found that nursing students with high emotional intelligence and moderate stress levels had positive correlations between their perceived stress and emotional intelligence [52].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies have indicated that undergraduate healthcare students have a higher score of emotional intelligence when assessed using the same measurement scale SSREIT [33] [55] . Furthermore, our study found that students experience a moderate level of stress, which aligns with a previous study that deployed the same PAS scale to measure academic stress in adolescents [45]. These ndings are in the same vein with a study carried out in Morocco by Ksiksou et al in 2023, which found that nursing students with high emotional intelligence and moderate stress levels had positive correlations between their perceived stress and emotional intelligence [52].…”
Section: Discussionsupporting
confidence: 92%
“…Statements 5,9,12,13 and 15 are on a reversed scale, with "strongly agree" equaling 1 and "strongly disagree" equaling 5. Felipe and Tatiane (2021) and Pontes et al (2023) reported high internal consistency (α= 0.83) and (α= 0.75) respectively [44] [45]. The overall Cronbach's alpha coe cient α in the study was 0.718, and Cronbach's alpha for the three subdomains were as follow: academic expectations (4 items; α= 0.789), workload and examinations (8 items; α= 0.866), and students' academic self-perceptions (6 items; α= 0.798).…”
Section: Perception Of Academic Stress Scale (Pas)mentioning
confidence: 99%
See 1 more Smart Citation